2009
DOI: 10.1055/s-0029-1238910
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Bone Disease in Cystic Fibrosis

Abstract: Patients with cystic fibrosis are frequently affected with pancreatic insufficiency and are predisposed to the development of diabetes mellitus (DM) and bone demineralization. Cystic fibrosis-related diabetes mellitus is a clinical entity distinct from type 1 and type 2 diabetes, with important implications for the nutritional and pulmonary health of cystic fibrosis patients. This form of diabetes owes largely to insulin deficiency, but alterations in insulin sensitivity and hepatic glucose production have als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 129 publications
0
9
0
1
Order By: Relevance
“…People with CF have multiple risk factors for inadequate bone mineralisation . Longitudinal studies have shown that bone gains during puberty are decreased in CF adolescents compared with healthy controls, resulting in decreased attainment of peak bone mass . A meta‐analysis reported that in CF, the prevalence of osteoporosis and osteopenia was 23.5% and 38%, respectively .…”
Section: Musculoskeletal Complications Of Cfmentioning
confidence: 99%
“…People with CF have multiple risk factors for inadequate bone mineralisation . Longitudinal studies have shown that bone gains during puberty are decreased in CF adolescents compared with healthy controls, resulting in decreased attainment of peak bone mass . A meta‐analysis reported that in CF, the prevalence of osteoporosis and osteopenia was 23.5% and 38%, respectively .…”
Section: Musculoskeletal Complications Of Cfmentioning
confidence: 99%
“…Despite the extensive scarring and destruction of the pancreas, the b-islet cells are relatively preserved initially. However, as patients become older, fibrosis of the islets occurs, resulting in a reduction in the number of insulin producing cells (10). This loss of insulin producing cells and relative insulin deficiency is the primary cause of CFRDM.…”
Section: Diseases Of Aging In Cystic Fibrosis: Diabetes Osteoporosismentioning
confidence: 99%
“…Hemoglobin A1c (HgbA1c) is not generally useful for screening (10). HgbA1c levels might not be elevated early in CFRDM due to the predominantly postprandial nature of the disease.…”
Section: Diseases Of Aging In Cystic Fibrosis: Diabetes Osteoporosismentioning
confidence: 99%
See 2 more Smart Citations